2023
DOI: 10.3390/diseases11020067
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidosis Type I Presenting with Persistent Neonatal Respiratory Distress: A Case Report

Abstract: Mucopolysaccharidosis type I (MPS I) is a rare inherited autosomal recessive lysosomal storage disorder. Despite several reports on MPS I-related neonatal interstitial lung disease, it is still considered to be an under-recognized disease manifestation. Thus, further study of MPS I is required to improve specific therapies and management strategies. The current report describes a late preterm baby (36 weeks gestational age) with neonatal onset of interstitial lung disease eventually diagnosed as MPS I. The neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As regards the primary involvement of the lung parenchyma in MPS patients, a study suggested the presence of direct alveolar and interstitial pulmonary damage due to GAG storage. Neonatal interstitial lung disease is an atypical presentation for MPS I, which is likely under-recognized and should be considered in the differential diagnosis of patients with persistent respiratory distress not controlled by multiple surfactant therapies after ruling out the common etiologies [ 32 ]. A few case reports described respiratory distress syndrome related to neonatal onset interstitial lung disease in newborns with a genetically confirmed diagnosis of MPS I [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…As regards the primary involvement of the lung parenchyma in MPS patients, a study suggested the presence of direct alveolar and interstitial pulmonary damage due to GAG storage. Neonatal interstitial lung disease is an atypical presentation for MPS I, which is likely under-recognized and should be considered in the differential diagnosis of patients with persistent respiratory distress not controlled by multiple surfactant therapies after ruling out the common etiologies [ 32 ]. A few case reports described respiratory distress syndrome related to neonatal onset interstitial lung disease in newborns with a genetically confirmed diagnosis of MPS I [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The WES was performed by PerkinElmer Genomics, Inc. (PerkinElmer, Waltham, MA, USA), the detailed method of which has been published previousl y . 10 The patient continued to require high cardiorespiratory support, but his medical condition worsened, and respiratory failure persisted. The patient died of severe respiratory failure at 16 days of life due to respiratory insufficiency secondary to a severely restricted thoracic cage.…”
Section: Case Descriptionmentioning
confidence: 99%
“…The WES was performed by PerkinElmer Genomics, Inc. (PerkinElmer, Waltham, MA, USA), the detailed method of which has been published previously. 10 The patient continued to require high cardiorespiratory support, but his medical condition worsened, and respiratory failure…”
Section: Case Descriptionmentioning
confidence: 99%
“…The direct sequencing of the amplified captured regions was performed using 2 × 150 bp paired end reads on NovaSeq 6000 Illumina next-generation sequencing (NGS) systems. The detailed method for WES has been published previously [21].…”
Section: Genetic Testingmentioning
confidence: 99%